2015
DOI: 10.3389/fphar.2015.00190
|View full text |Cite|
|
Sign up to set email alerts
|

Salvinorin A, a kappa-opioid receptor agonist hallucinogen: pharmacology and potential template for novel pharmacotherapeutic agents in neuropsychiatric disorders

Abstract: Salvinorin A is a potent hallucinogen, isolated from the ethnomedical plant Salvia divinorum. Salvinorin A is a selective high efficacy kappa-opioid receptor (KOPr) agonist, and thus implicates the KOPr system and its endogenous agonist ligands (the dynorphins) in higher functions, including cognition and perceptual effects. Salvinorin A is the only selective KOPr ligand to be widely available outside research or medical settings, and salvinorin A-containing products have undergone frequent non-medical use. KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 81 publications
0
48
0
1
Order By: Relevance
“…However, concerns remain about safety and toxicity of ibogaine, tempering the widespread implementation of ibogaine research and treatment for the time being (Alper et al, 2012; Hoelen et al, 2009). Preclinical data and basic human research on Salvinorin A (SA) suggest an important role for the Kappa opioid receptor system in modulating addiction, mood, and consciousness (Addy et al, 2012; 2015; Freeman et al, 2014; Johnson et al, 2011; 2016); though clinical research has yet to provide evidence for therapeutic use of SA, which remains an important direction for future research (Butelman & Kreek, 2015; Chavkin, 2011). Cannabis and the cannabinoids have shown therapeutic value as a treatment for chronic pain, spasticity in multiple sclerosis, and chemotherapy induced nausea (Whiting et al, 2015), with a number of other conditions such as cancer, epilepsy, sleep disorders, and PTSD implicated as possible targets for cannabis-based treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerns remain about safety and toxicity of ibogaine, tempering the widespread implementation of ibogaine research and treatment for the time being (Alper et al, 2012; Hoelen et al, 2009). Preclinical data and basic human research on Salvinorin A (SA) suggest an important role for the Kappa opioid receptor system in modulating addiction, mood, and consciousness (Addy et al, 2012; 2015; Freeman et al, 2014; Johnson et al, 2011; 2016); though clinical research has yet to provide evidence for therapeutic use of SA, which remains an important direction for future research (Butelman & Kreek, 2015; Chavkin, 2011). Cannabis and the cannabinoids have shown therapeutic value as a treatment for chronic pain, spasticity in multiple sclerosis, and chemotherapy induced nausea (Whiting et al, 2015), with a number of other conditions such as cancer, epilepsy, sleep disorders, and PTSD implicated as possible targets for cannabis-based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…SA, in contrast, leads to conditioned place aversion and decreased intracranial self-stimulation (Carlezon et al, 2006; Sufka et al, 2014). Dynorphins, the endogenous ligands for the KOR have been implicated in many adverse behaviors including stress-induced drug relapse in animal models (Beardsley et al, 2005) and have been proposed as important therapeutic targets for addiction treatments (Butelman & Kreek, 2015; Chavkin, 2011;). SA may also have downstream effects on the endocannabinoid system (Braida et al, 2007; 2008), but this has not yet been demonstrated in primates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in animal models have revealed that Salvinorin A exerts a number of pharmacological actions of potential therapeutic interest which are not solely limited to the central nervous system (Butelman and Kreek, 2015). These include attenuation of inflammation (Aviello et al, 2011; Rossi et al, 2016), inhibition of intestinal motility (Capasso et al, 2008), and antipruritic effects (Salaga et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with brain‐accessible agonists, the analgesic effects of peripherally restricted agonists are not accompanied by sedative effect, respiratory depression or abuse potential. However, when KOR agonists penetrate the brain, they cause hallucination, dysphoric effects and aversion . Second‐messenger studies suggest that the dysphoric effects of KOR agonists involve G protein‐coupled recruitment of ÎČ‐arrestin and activation of p38 MAPK (mitogen‐activated protein kinase), whereas the analgesic effect is independent of such downstream signalling .…”
Section: What Is Known and Objectivementioning
confidence: 99%